Short-term menthol treatment promotes persistent thermogenesis without induction of compensatory food consumption in Wistar rats: implications for obesity control - Lillo Vizin, Robson Cristiano; Motzko-Soares, Anna Carolina P.; Armentano, Giovana Marchini; Ishikawa, Debora T.; Cruz-Neto, Ariovaldo P. [UNESP]; Carrettiero, Daniel Carneiro; Almeida, Maria Camila (Amer Physiological Soc, 2018)
In this study, we aimed to evaluate the influence of daily repeated menthol treatments on body mass and thermoregulatory effectors in Wistar rats, considering that menthol is a transient receptor potential melastatin 8 channel agonist that mimics cold sensation and activates thermoregulatory cold-defense mechanisms in mammals, promoting hyperthermia and increasing energy expenditure, and has been suggested as an anti-obesity drug. Male Wistar rats were topically treated with 5% menthol for 3 or 9 consecutive days while body mass, food intake, abdominal temperature, metabolism, cutaneous vasoconstriction, and thermal preference were measured. Menthol promoted hyperthermia on all days of treatment, due to an increase in metabolism and cutaneous vasoconstriction, without affecting food intake, resulting in less mass gain in menthol-hyperthermic animals. As the treatment progressed, the menthol-induced increases in metabolism and hyperthermia were attenuated but not abolished. Moreover, cutaneous vasoconstriction was potentiated, and an increase in the warmth-seeking behavior was induced. Taken together, the results suggest that, although changes occur in thermoeffector recruitment during the course of short-term treatment, menthol is a promising drug to prevent body mass gain. NEW & NOTEWORTHY Menthol produces a persistent increase in energy expenditure, with limited compensatory thermoregulatory adaptations and, most unexpectedly, without affecting food intake. Thus short-term treatment with menthol results in less mass gain in treated animals compared with controls. Our results suggest that menthol is a promising drug for the prevention of obesity.
Keywords: body mass; cold defense; hyperthermia; thermoregulation; TRPM8